Using Earthquakes, T Waves, and Infrasound to Investigate the Eruption of Bogoslof Volcano, Alaska. Issue 14 (25th July 2018) - Wech, Aaron; Tepp, Gabrielle; Lyons, John; Haney, Matt
Abstract: The 2016–2017 eruption of Bogoslof volcano, a submarine stratovolcano in the Bering Sea, produced 70 discrete explosive eruptions over 8 months. With no local monitoring data, activity was seismically recorded on nearby islands 50–100 km away, limiting the detection and resolution of seismic observations. We construct a matched filter catalog of 3, 199 events from 49 earthquake families, many of which occurred with hydroacoustic T waves of varying strength. We then use a 2‐D finite difference model to show that hydroacoustic amplitudes should decrease with increased source depth beneath the edifice and leverage each family's seismically recorded T wave amplitude as a proxy for source depth, which we compare to regional infrasound data. This unique combination of using P and S waves to detect events, T waves as a proxy for depth, and infrasound for precise timing of emissions allows us to interpret the dynamics and evolution of the Bogoslof eruption. Plain Language Summary: The eruption of Bogoslof volcano, Alaska, primarily occurred underwater, making it difficult to track and interpret activity. We use instruments on neighboring islands to track eruption energy traveling through the Earth, ocean, and atmosphere. We use different techniques to investigate each signal, which results in a unique combination of data sets. This novel approach provides insights into the dynamics and evolution of the Bogoslof eruption, otherwise impossible with conventional means, and could be applied to other submarine eruptions. Key Points: We combine template matching, T wave amplitudes, and infrasound to probe a submarine eruption of a locally unmonitored volcano Numerical model predicts depth dependence of T wave amplitude, which we use to interpret non‐eruptive, pre‐eruptive, co‐eruptive, and post‐eruptive seismicity Results provide framework for understanding dynamics and evolution of Bogoslof eruption, and approach has applications to future eruptions